Perencanaan Pembangunan Jalan Griya Abdi Negara Kota Pagar Alam - Masagus Taswin; Ari Abdul Kadir (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
Fences nature one of the cities that is growing both in the field and in the economy inprastruktur. Transportation is a means of support in the development in an area, transportation improvements are very necessary for the development of an area. Gria servant of the state is a new housing in the city of Pagar Alam who is still in the process of increasing the field inprstruktur. Road access in and out in a residential neighborhood still land and no building pavement. This study was conducted to plan pengunana access roads in and out of the housing Gria servant negra. Type of pavement is planned or rigid pavement using concrete cast. Based on the calculation results obtained 150mm thick layer of concrete pavement with reinforcement in the transverse direction and reinforcement of the longitudinal direction D12-250mm D12-150mm.